Why I am not a Hindu : a Sudra critique of Hindutva philosophy, culture and political economy - Ilaiah, K. (Kancha), 1952- (SAGE Publications India Pvt Ltd, 2019)
This noted bestseller, which introduced the concept of Dalitization, acts as a manifesto for the Dalitbahujans of India to this day.